A temporal examination of inspiratory muscle strength and endurance in hospitalized COVID-19 patients - Dosbaba, Filip; Hartman, Martin; Batalik, Ladislav; Senkyr, Vojtech; Radkovcova, Ivana; Richter, Svatopluk; Brat, Kristian; Cahalin, Lawrence P; Formiga, Magno F (Heart & lung, 2023)
BACKGROUND: The two most common symptoms associated with COVID-19 are dyspnea and fatigue. One possible cause of such symptoms may be inspiratory muscle weakness. OBJECTIVES: The purpose of this study was to examine inspiratory muscle performance (IMP) from intensive care unit discharge (ICUD) to hospital discharge (HD) in patients with COVID-19 hypothesizing that IMP would be markedly depressed at both ICUD and HD. METHODS: IMP was examined at ICUD and HD via the PrO2 device (PrO2 Health, Smithfield, RI) which provided the maximal inspiratory pressure (MIP), sustained MIP (SMIP), inspiratory duration (ID), and fatigue index test (FIT). Patient symptoms were assessed at ICUD, HD, and 1-month post-HD. RESULTS: 30 patients (19 men, 11 women) with COVID-19 were included. The mean±SD age, BMI, and length of ICU and hospital stay was 71±11 yrs, 27.9 ± 6.3 kg/m, 9 ± 6 days, and 26±16 days, respectively. The mean±SD MIP, SMIP, ID, and FIT of the entire cohort at ICUD vs HD were 36±21 vs 40±20 cm H2O, 231±157 vs 297±182 PTU, 8.8 ± 4.2 vs 9.5 ± 4.6 s, and 9.0 ± 9.4 vs 13.1 ± 12.3, respectively, with only SMIP and FIT significantly greater at HD (p=.006 and 0.03, respectively). SMIP at HD was significantly related to resting dyspnea at HD (r=-0.40; p=.02). The SMIP and FIT of men were found to increase significantly from ICUD to HD, but no measure of IMP in the women increased significantly from ICUD to HD. At least one COVID-19-related symptom was present 1 month after HD with the most persistent symptoms being fatigue, cough, and dyspnea in 47%, 40%, and 37% of the patients, respectively. CONCLUSIONS: A significant reduction in IMP exists in patients with COVID-19 at both ICUD and HD and no measure of IMP in women was observed to increase significantly from ICUD to HD. Impaired inspiratory muscle endurance rather than strength was associated with greater dyspnea at HD.
Keywords: dechová cvičení; Female; Breathing Exercises; dyspnoe; Test of Incremental Respiratory Endurance; ženské pohlaví; svalová síla; lidé; Dyspnea; Inspiratory muscle performance; Aged, 80 and over; COVID-19; Muscle Strength; Male; Inspiratory muscle endurance; Aged; Maximal inspiratory pressures; Respiratory Muscles; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; dýchací svaly; Middle Aged; Humans